Oxidative stress increases Fas ligand expression in endothelial cells - Nagai Atsushi; Aoshiba Kazutetsu; Suzuki Mayumi (BMC, 2006)
Abstract Background Fas ligand (FasL) induces apoptosis in Fas-bearing target cells, such as leukocytes, and up-regulation of FasL expression on the endothelium may contribute to anti-inflammatory reactions that attenuate leukocyte extravasation during inflammation. Since oxidants generated during inflammation and cigarette smoking may modulate endothelial function, we examined the effect of H2O2 and cigarette smoke on endothelial FasL expression. Methods Human umbilical vein endothelial cells (HUVECs) were exposed to nontoxic concentrations of H2O2 and cigarette smoke extracts (CSE). Membrane FasL expression was assessed by immunostaining with anti-FasL antibody followed by either monolayer-cell-based spectrofluorimetry or flow cytometry. Soluble FasL in culture supernatants was measured by enzyme-linked immunosorbent assay. For the cytotoxic assay, HUVECs were exposed to H2O2 and co-cultured with neutrophils. Neutrophils were stained by a peroxidase/diaminobenzidine-based reaction, and apoptosis was evaluated on the basis of nuclear morphology after Giemsa staining. To analyze in vitro FasL expression in arteries, rat thoracic aortas were incubated with H2O2, and paraffin-embedded sections were prepared for immunohistochemistry with anti-FasL antibody. Results Exposure of HUVECs to H2O2 dose-dependently increased their levels of both membrane and soluble forms of FasL expression. CSE exposure also caused increased levels of FasL expression, but the increase was partially inhibited by the addition of catalase. When co-cultured with neutrophils, HUVECs exposed to H2O2 significantly promoted neutrophil apoptosis. Rat thoracic aortas incubated with H2O2 exhibited increased FasL expression on their endothelium. Conclusion Low levels of oxidative stress increase FasL expression on endothelial cells, thereby potentially reducing leukocyte extravasation and tissue damage.